2018
DOI: 10.26842/binhm.7.2018.15.1.0093
|View full text |Cite
|
Sign up to set email alerts
|

First Record of Aenasius Arizonensis (Girault, 1915) (Hymenoptera, Encyrtidae), a Parasitoid of Phenacoccus Solenopsis Tinsly, 1898 (Hemiptera, Pseudococcidae) in Iraq

Abstract: This article reports the first record of Aenasius arizonensis (Girault, 1915) (Hymenoptera, Encyrtidae) parasitizing the recently introduced species of cotton mealybug, Phenacoccus solenopsis Tinsly (Hemiptera, Psedococcidae) infesting Lantana camara L. (Verbeneceae) as well as other ornamental plants in Baghdad province, Iraq. A short morphological description is also presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…This species of the parasitoid is characterized by a set of important characteristics, including the ability to adapt to different environmental conditions, and its life cycle is short and multiplies faster than its host and has a great ability to search for a host and its life cycle coincides with the life cycle of the host, and this species recorded a percentage of parasitism ranging between 5-100% (Fallahzadeh et al, 2014). The parasitoid was counted and identified in different parts of the world, including USA, India, Pakistan, China, Iran, Egypt, Turkey and Iraq (Abdul-rassoul, 2018). The researchers Solangi and Mahmood (2011) studied the parasitoid, A. arizonensis ability to parasitize on six different types of mealybugs and their ability to grow and develop the parasitoid.…”
Section: Introductionmentioning
confidence: 99%
“…This species of the parasitoid is characterized by a set of important characteristics, including the ability to adapt to different environmental conditions, and its life cycle is short and multiplies faster than its host and has a great ability to search for a host and its life cycle coincides with the life cycle of the host, and this species recorded a percentage of parasitism ranging between 5-100% (Fallahzadeh et al, 2014). The parasitoid was counted and identified in different parts of the world, including USA, India, Pakistan, China, Iran, Egypt, Turkey and Iraq (Abdul-rassoul, 2018). The researchers Solangi and Mahmood (2011) studied the parasitoid, A. arizonensis ability to parasitize on six different types of mealybugs and their ability to grow and develop the parasitoid.…”
Section: Introductionmentioning
confidence: 99%
“…This is due to the fact that, this parasitoid has some characteristics of adaptation to different environmental conditions, multiply faster than the host, short life Cycle (17-20 days), high host searching capacity and synchronise life cycle with host, with a parasitism ranging from 5-100% [8]. The parasitoid was recorded from USA, India, Pakistan, China, Iran, Egypt, Turkey and Iraq [9,13] One of the researchers [14] The present study was carried out to evaluate some of the biological characteristics of this parasitoid, to be applied as a bio-control agent for cotton Mealy bug, P. solenopsis in Sudan. [14,20] who showed that, the parasitized Mealy bug took a week to transform into mummy feature ( Fig.1 and Fig2).…”
Section: Introductionmentioning
confidence: 99%
“…This increases the chances of obtaining realistic predictions for the period and area outside (Spradbery et al 1992), Iran in 1995 (Navidpour et al 1996), and Iraq in 1996. OWS was first reported in Iraq in June 1996 (Abdul Rassoul et al 1996), and the monthly incidence showed two major peaks, respectively in the winters of 1996 and 1997, until 1998 when insecticide formulations became finally available to the veterinary clinics and the incidence reduced ( Fig.1 Siddig et al 2005) As illustrated in Fig. 1 the geographic distribution of OWS clinical cases was only recorded for the period September 1996 to October 1997 (Oct. 97 is incomplete).…”
mentioning
confidence: 99%